Energy‐dispersive Laue diffraction by means of a pnCCD detector coupled to a CsI(Tl) scintillator using ultra‐hard X‐ray synchrotron radiation. (25th July 2019) - Shokr, Mohammad; Tosson, Amir; Abboud, Ali; Algashi, Alaa; Schlosser, Dieter; Hartmann, Robert; Klaus, Manuela; Genzel, Christoph; Strüder, Lothar; Pietsch, Ullrich
Abstract : Determination of the lattice parameters, unit‐cell orientation and structure factors of SrLaAlO4 crystal by means of energy‐dispersive X‐ray Laue diffraction using ultra‐high X‐ray synchrotron radiation and 2D energy‐dispersive detector. Abstract : The lattice parameters and unit‐cell orientation of an SrLaAlO4 crystal have been determined by means of energy‐dispersive X‐ray Laue diffraction (EDLD) using a pnCCD detector coupled to a columnar structure CsI(Tl) scintillator in the energy range between 40 and 130 keV. By exploiting the high quantum efficiency (QE) achieved by this combined detection system for hard X‐rays, a large number of Bragg reflections could be recorded by the relatively small detector area, allowing accurate and fast determination of the lattice parameters and the moduli of the structure factors. The experiment was performed on the energy‐dispersive diffraction (EDDI) beamline at the BESSY II synchrotron using a pnCCD detector with 128 × 128 pixels. Since the energies and positions of the Laue peaks can be recorded simultaneously by the pnCCD system, the tetragonal structure of the investigated specimen was determined without any prior information. The unit‐cell parameters and the angles between the lattice vectors were evaluated with an accuracy of better than 0.7%, while the structure‐factor moduli of the reflections were determined with a mean deviation of 2.5% relative to the theoretical values.